Report on Staffing and Salaries, Fall 1995 - California Community Colleges, Sacramento. Office of the Chancellor; California Community Colleges, Sacramento. Office of the Chancellor ([S.l.] : Distributed by ERIC Clearinghouse, 1997)
Fifteenth in a series of annual reports, this document presents fall 1995 demographic, staffing, salary, and workload information on California community college employees, based on data collected from all 71 college districts. Section I presents district- and college-level data on the number of employees by primary occupational activity, full-time equivalent (FTE) employees by occupational activity, numbers of employees and FTE employees by category, percent distribution and total number of weekly faculty contact hours taught, and numbers of full-time faculty and salaries paid from 1992-93 to 1995-96. Sections II through VIII then summarize data for each of the seven major categories of employees: full-time faculty; temporary and part-time faculty; professional employees, including faculty who spend more than 15 hours per week as counselors, librarians, or nurses; certificated administrators; classified administrators; classified non-administrative employees; and casual employees. For each group, tables provide data on percentage distributions by age, gender, and ethnicity; numbers and percent distribution by employment classification, employment status, and duration of employment contract/agreement; and annual salary per schedule plus stipends; while faculty tables also provide data on weekly faculty contact hours, weekly faculty contact hours of overload instruction, and hourly compensation rate for overload instruction. (HAA)
ERIC Note: For the fall 1994 report, see JC 970 317.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrators; College Faculty; Community Colleges; Compensation (Remuneration); Faculty Workload; Full Time Equivalency; Full Time Faculty; Institutional Characteristics; Part Time Faculty; Personnel Data; Salaries; School Personnel; Staff Utilization; State Surveys; Teacher Salaries; Two Year Colleges; California Community Colleges; Numerical/Quantitative Data; Reports, Descriptive